Initial Checklist of Butterflies (Lepidoptera: Rhopalocera) in Punti Kayu Recreation Forest, Palembang, South Sumatra - Ina Aprillia; Octavia Susilowati; Dian Mutiara; Muhammad Iqbal (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2025)
The Punti Kayu Recreation Forest is a managed urban green space in Palembang City, South Sumatra Province, Indonesia. Over three survey periods in 2010, 2012, and 2019, a total of 16 butterfly species from five families were recorded. The Nymphalidae family was the most dominant, with an increasing trend in species richness observed over time. The findings highlight the importance of urban green spaces for supporting butterfly diversity and emphasize the need for continued conservation efforts, including the creation of butterfly-friendly habitats and protection of existing green spaces.